Defect engineering strategy to enhance the SO2 adsorption performance of Zr-based MOFs materials: potential application for purifying cultural heritage storage environments - Meirong Shi; Zejin; Yongjin Wang; Nan Jia; Zhongping Sha; Peng Fu (Heritage Science)
Abstract In this work, a novel Zr-based MOFs material (D-NH2-UiO-66) with multi-stage pore structure was prepared by introducing defects in NH2-UiO-66 through a ligand regulation strategy, aiming to enhance the SO2 adsorption performance and be applied to purify the cultural relic storage environment. The research demonstrated that the defect engineering effectively increased the pore diameter of the precursor material, leading to the exposure of internal adsorption sites within the framework and the utilization of defect sites, thereby increasing the number of adsorption sites. Moreover, the enlargement of pore diameter facilitated the diffusion of gas molecules within the framework, which enhanced the mass transfer process. Density Functional Theory (DFT) calculations were conducted to deeply investigate the impact of defect structures on the adsorption mechanism. In addition, breakthrough experiments were conducted to assess the adsorption performance of D-NH2-UiO-66 towards SO2, and the material’s potential application in cultural relic storage environments was explored through controlled laboratory tests. The results indicated that this material possesses outstanding SO2 adsorption performance, effectively improving the integrity of paper fibers and enhancing the tensile strength of the paper. This study not only provides new insights into the application of MOFs materials in environmental protection but also offers an effective solution for the preservation of cultural heritage.